The Power of Intangible Resources for Cause Champions in Sport‐For‐Development: A Singapore Case Study - Sophia Harith; Mathieu Marlier; Wai Cheong Eugene Chew; Mathieu Winand; Annick Willem (Social Inclusion, 2025)
Cause champions are recognised to play a meaningful role in supporting the delivery and impact of sport‐for‐development (SFD) programmes. They are individuals who emerge from a programme’s target community and assume a leadership role to advocate for social change. However, there remains limited empirical inquiry on the factors that enable cause champions to thrive. Therefore, this study explored the most essential resources needed for cause champions to succeed in SportCares, an SFD organisation in Singapore. In total, 18 semi‐structured interviews were conducted with staff members, coaches, and cause champions. Three essential resources were identified: sustained tangible resources (i.e., funding and physical infrastructure), invested human capital (i.e., staff and coaches’ efforts), and organisational capital of emotional authenticity (i.e., sincerity through communication). The findings demonstrated that the interaction of these resources fostered a culture of care that supported the champion’s ability to advocate for social change. These results urge monitoring, evaluation, and learning (MEL) practices to focus more on intangible and relational processes such as co‐creation sessions and authentic storytelling.